Allocation of time and cost in project management using goal programming case study: Teras Chuping Enterprise / Nur Athirah Amir Hamzah - Amir Hamzah, Nur Athirah (2020)
The allocation of time and cost in a project have always become a common issue faced by most of the company. In the real-life activity, the project manager needs to handle multiple issues that arise regarding the project management such as the projects are not completed on time and the cost is over budget. This paper discusses about the application of preemptive goal programming model to allocate time and cost in few projects at Teras Chuping Enterprise, a metal welding and fabrication company. The data was analyzed using LINGO 17 software. The results show that when the first priority is to complete the project on time, the priority to keep the project expenditure within the budget is not fully achieved with some projects are above the budget and some projects are below the budget.